Implementasi Metode Vogel’s Approximation Method Pada Pengoptimalan Biaya Pengiriman Barang Pada CV. Expres Nias - Ndruru, Eferoni; Hutabarat, Sumiaty Adelina (LPPM UNIKA Santo Thomas Medan, 2018)
Operations Research is one way of taking decisions in companies by formulating problems of daily life with mathematical models with the aim of getting optimal goals. Transportation problems are one of the problems in solving operational research problems with the aim of optimizing distribution costs of shipping goods from the first warehouse to the destination warehouse. Like the problem that is in cv. Express nias where the cost of shipping goods does not calculate the optimal cost sometimes losses and profits are not optimal. The method used in solving this problem is the method of Vernel's approximation method, this method is included with the method of transportation. The results obtained in this study are that all shipping costs for cv.express nias are optimal.